Cultural Semiotics Analysis of Traditional Bantengan Art: Exploring Function, Symbolic Meaning, Moral Significance, and Existence - Sawitri; Ummul Khasanah; Ishak Bagea; Ria Kristia Fatmasari; Pande Wayan Renawati (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Traditional Bantengan art is not only a rich cultural heritage laden with meanings and symbolism but also reflects the richness and complexity of society. This research aims to explore the functions, symbolic meanings, moral significance, and existence of traditional Bantengan art through the lens of cultural semiotics. Through the cultural semiotics approach, various elements such as gestures, music, and visual symbols in Bantengan performances are dissected to understand the complexity and diversity of meanings created. Furthermore, this research explores the adaptation and evolution of Bantengan art in the context of social, political, and economic dynamics in the era of globalization. This is a qualitative study, with data focusing on functions, symbolic meanings, moral significance, and existence, sourced from traditional Bantengan art. The method used to collect data is the participatory observation method. Researchers observe traditional Bantengan performances through recording and note-taking techniques. Additionally, interviews are conducted with religious figures, elders, artists, cultural experts, and the communities of Mojokerto and Malang, along with document analysis. After data collection, the researcher reduces and classifies the data by type. Subsequently, the researcher verifies and codes the data according to its type. The interpreted data is then presented in tables. The results of the research indicate that traditional Bantengan art encompasses various functions, symbolic meanings, and moral messages reflecting the spirit of courage, solidarity, and sacrifice of the community during the resistance against the Dutch colonialists. Nevertheless, the existence of Bantengan art in the cities of Malang and Mojokerto remains enduring, signifying its value and continuity within local culture